2013
DOI: 10.1371/journal.pone.0075673
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Approaches to Identifying Migration Chronology in a Continental Migrant

Abstract: The degree to which extrinsic factors influence migration chronology in North American waterfowl has not been quantified, particularly for dabbling ducks. Previous studies have examined waterfowl migration using various methods, however, quantitative approaches to define avian migration chronology over broad spatio-temporal scales are limited, and the implications for using different approaches have not been assessed. We used movement data from 19 female adult mallards (Anas platyrhynchos) equipped with solar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…We defined a transmitter failure or mortality event as the disappearance of signal or consistent and sequential locations that were ≤100 m from the last recorded location for each individual. Elsewhere (Beatty et al ), we reported the migration chronology for each of the wild mallards using net displacement methods (see Bunnefeld et al ), which were used to exclude breeding season movements of marked birds.…”
Section: Methodsmentioning
confidence: 99%
“…We defined a transmitter failure or mortality event as the disappearance of signal or consistent and sequential locations that were ≤100 m from the last recorded location for each individual. Elsewhere (Beatty et al ), we reported the migration chronology for each of the wild mallards using net displacement methods (see Bunnefeld et al ), which were used to exclude breeding season movements of marked birds.…”
Section: Methodsmentioning
confidence: 99%
“…ND measures the straight line distance between the first location (i.e. the trapping location) and all subsequent relocations for an individual animal (Bunnefeld et al 2011, Beatty et al 2013. We calculated daily ND values for each bird with the first relocation recorded each day.…”
Section: Individual-level Migration Parametersmentioning
confidence: 99%
“…NSD, which is the Euclidian squared distance between the first location of a segment and any consecutive relocations, is an effective method to characterize GPS data because it transforms movement data from 3D (x, y, t) to 2D (x from origin, t) permitting the application of simpler statistical models (B€ orger & Fryxell 2012). NSD is commonly used to model migratory movement of animals at very large scales (Bunnefeld et al 2011;Singh et al 2012;Beatty et al 2013), but can logically be applied to smaller-scale movements.…”
Section: S T E P 1 : S E G M E N T I N G G P S T R a C K I N T O M E mentioning
confidence: 99%